2020
DOI: 10.3389/fpsyg.2020.01832
|View full text |Cite
|
Sign up to set email alerts
|

No Bilingual Benefits Despite Relations Between Language Switching and Task Switching

Abstract: Previous research has shown that bilingual children outperform monolinguals on tasks testing cognitive control. Bilinguals' enhanced cognitive control is thought to be caused by the necessity to exert more language control in bilingual compared to monolingual settings. Surprisingly, between-group research of cognitive effects of bilingualism is hardly ever combined with within-group research that investigates relationships between language control and cognitive control. The present study compared 27 monolingua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 73 publications
1
5
1
Order By: Relevance
“…In addition, previous research that has investigated low-SES populations has found that although bilinguals maintain lower vocabulary scores compared to monolinguals, their performance on cognitive tasks remains high (Meir & Armon-Lotem, 2017). However, our study cannot explain why other studies with similar populations find no bilingual advantage (Timmermeister et al, 2020). We suggest that perhaps one way forward in the literature is to test for significant predictors, including SES, to identify what additional factors could be contributing to these differences in the literature.…”
Section: Discussioncontrasting
confidence: 87%
“…In addition, previous research that has investigated low-SES populations has found that although bilinguals maintain lower vocabulary scores compared to monolinguals, their performance on cognitive tasks remains high (Meir & Armon-Lotem, 2017). However, our study cannot explain why other studies with similar populations find no bilingual advantage (Timmermeister et al, 2020). We suggest that perhaps one way forward in the literature is to test for significant predictors, including SES, to identify what additional factors could be contributing to these differences in the literature.…”
Section: Discussioncontrasting
confidence: 87%
“…In a recent study of a large sample of 9- and 10-year-old children (n = 4524), Dick and colleagues32 found no evidence for a bilingual advantage for cognitive skills associated with executive functioning. Among 5- to 8-year-olds, Timmermeister and colleagues33 also reported no bilingual benefit for cognitive control. Consistent with Baralt and Darcy Mahoney,25 we argue that these disparate findings may result from differences in the way in which bilingualism was operationalized.…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with Baralt and Darcy Mahoney,25 we argue that these disparate findings may result from differences in the way in which bilingualism was operationalized. For example, Dick and colleagues32 included bilingual children with only receptive ability as well as bilingual children with productive ability in their sample (“Besides English, do you speak or understand another language or dialect?”32 (p698) ) Timmermeister and colleagues33 also reported null findings; however, they operationalized bilingualism as having at least one parent speak Turkish in the home environment, where the mainstream language was Dutch; the researchers did not evaluate children's language abilities. As reported earlier, the only other study to date that has examined bilingualism in preterm-born populations, Loe and Feldman,24 operationalized bilingualism as at least 10 hours per week of “exposure”; they also found null results.…”
Section: Discussionmentioning
confidence: 99%
“…The so-called "bilingual advantage hypothesis" is controversial and hotly debated. Several studies have failed to replicate bilingual advantages in inhibition, cognitive flexibility, and working memory for both children and adults (e.g., Paap and Greenberg, 2013;Gathercole et al, 2014;Dick et al, 2019;Timmermeister et al, 2020). Furthermore, several meta-analyses .…”
Section: Bilingualism and Advantages In Executive Functionmentioning
confidence: 99%